In silico studies, synthesis and pharmacological evaluation to explore multi-targeted approach for imidazole analogues as potential cholinesterase inhibitors with neuroprotective role for Alzheimer's disease. Issue 8 (1st May 2018) - Gurjar, Archana S.; Darekar, Mrunali N.; Yeong, Keng Yoon; Ooi, Luyi
Graphical abstract: Highlights: Docking studies of 2-substituted-4, 5-diphenyl-1H-imidazoles in AChE active site. Based on Docking and in silico ADME results, synthesis of some analogues. Study neuroprotective role, toxicity and effect of analogues on memory in animals. Detailed mechanistic in vitro AChE and BuChE inhibition studies. Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder with multiple factors associated with its pathogenesis. Our strategy against AD involves design of multi-targeted 2-substituted-4, 5-diphenyl-1H-imidazole analogues which can interact and inhibit AChE, thereby, increasing the synaptic availability of ACh, inhibit BuChE, relieve induced oxidative stress and confer a neuroprotective role. Molecular docking was employed to study interactions within the AChE active site. In silico ADME study was performed to estimate pharmacokinetic parameters. Based on computational studies, some analogues were synthesized and subjected to pharmacological evaluation involving antioxidant activity, toxicity and memory model studies in animals followed by detailed mechanistic in vitro cholinesterase inhibition study. Amongst the series, analogue 13 and 20 are the most promising multi-targeted candidates which can potentially increase memory, decrease free radical levels and protect neurons against cognitive deficit.